2017
DOI: 10.1039/c7cp05864k
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic identification of the chemical interplay between defects and dopants in Al-doped ZnO

Abstract: The conduction and optoelectronic properties of transparent conductive oxides can be largely modified by intentional inclusion of dopants over a very large range of concentrations. However, the simultaneous presence of structural defects results in an unpredictable complexity that prevents a clear identification of chemical and structural properties of the final samples. By exploiting the unique chemical sensitivity of Hard X-ray Photoelectron Spectra and Near Edge X-ray Absorption Fine Structure in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…The same compression was assigned in previous works to the presence of defects in the oxide [50,51]. We previously demonstrated that our ZnO films grown at RT in Ar are over-stoichiometric in oxygen, due to the presence of Zn vacancies and O interstitials [29]. Further indications of the crystalline quality of the film are the 2θ (0002) and the rocking curve (RcC) full width at half maximum (FWHM) across the Bragg diffraction peak.…”
Section: Temperature Optimizationsupporting
confidence: 84%
See 2 more Smart Citations
“…The same compression was assigned in previous works to the presence of defects in the oxide [50,51]. We previously demonstrated that our ZnO films grown at RT in Ar are over-stoichiometric in oxygen, due to the presence of Zn vacancies and O interstitials [29]. Further indications of the crystalline quality of the film are the 2θ (0002) and the rocking curve (RcC) full width at half maximum (FWHM) across the Bragg diffraction peak.…”
Section: Temperature Optimizationsupporting
confidence: 84%
“…The same compression was assigned in previous works to the presence of defects in the oxide [ 50 , 51 ]. We previously demonstrated that our ZnO films grown at RT in Ar are over-stoichiometric in oxygen, due to the presence of Zn vacancies and O interstitials [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…0 4  % was chosen because it has already been reported that it is the optimum doping level for highly conductive and transparent AZO films 18 . Increasing doping above this value induces the appearance of states in the gap near the valence band maximum, which are related to the defects introduced in the oxide, that reduce the number of free carriers and probably also their mobility 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Among these heavier elements, there are several transition metals of particular interest to researchers, i.e., Fe, Co, Ni, Cu, Zn, as well as their oxides [ 14 , 15 ] and compounds [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. These interests are related to their magnetic [ 23 , 24 ], optical [ 25 ], as well as conductive and semi-conductive [ 20 , 21 , 26 ] properties, which in turn translate to possible applications in catalytic, photocatalytic and photoelectrocatalytic (PEC) processes [ 14 , 27 , 28 , 29 ], as electrodes in photovoltaic cells and lithium-ion batteries [ 30 , 31 , 32 ], optoelectronic and plasmonic devices [ 15 , 25 , 33 ], gas sensors [ 34 ] or drug delivery [ 16 , 35 ].…”
Section: Introductionmentioning
confidence: 99%